Phosphorus removal by in situ generated Fe(II): Efficacy, kinetics and mechanism. (1st June 2018) - Zhang, Jiao; Bligh, Mark W.; Liang, Peng; Waite, T. David; Huang, Xia
Abstract: The application of in situ electrochemical generation of ferrous (Fe(II)) ions for phosphorus (P) removal in wastewater treatment was investigated with attention to the efficacy, kinetics and mechanism. At concentrations typical of municipal wastewater, P could be removed by in situ Fe(II) with removal efficiency higher than achieved on addition of FeSO4 and close to that of FeCl3 under both anoxic and oxic conditions. The generation of alkalinity due to water electrolysis at the cathode created much higher pH conditions compared to FeSO4 dosing thereby resulting in very different pathways of Fe solid phase formation and associated P removal mechanisms. The remarkably similar dependence of P removal on accumulated Fe for all investigated currents, initial P concentrations and DO conditions indicated that kinetic aspects did not play a role in P removal during in situ Fe(II) dosing. Thermodynamic modelling was undertaken to investigate possible solid phase formation pathways under anoxic conditions and these insights were extended to oxic conditions. The exclusive formation of ferrous hydroxide during anoxic in situ Fe(II) dosing implied that P removal occurred via coprecipitation and adsorption. Under oxic conditions, the high pH conditions would have resulted in rapid Fe(II) oxidation and formation of ferric oxyhydroxides with associated coprecipitation and adsorption effecting P removal in a similar pattern to that observed under anoxic conditions. In situ Fe(II) dosing represents a versatile option for chemical P removal with the precise control of Fe dosage to optimize FeP forms for possible P recovery. Graphical abstract: Highlights: In situ Fe(II) had higher phosphorus removal efficiency than FeSO4 with rising pH. Kinetics was not a crucial aspect for phosphorus removal by in situ Fe(II). Ferrous hydroxide was the major in situ Fe(II) precipitate under anoxic condition. Amorphous ferric oxyhydroxide was the major iron precipitate under oxic condition. Phosphorus was predominantly removed through coprecipiation and adsorption.